Local self-government bodies and military administrations: current problems of functioning under martial law - V. S. Govorov (Bulletin of Kharkiv National University of Internal Affairs)
Russia's large-scale invasion into Ukraine has become a new challenge for society and the government and has provoked a number of crises and problems that seriously complicate the functioning of the state. Presidential Decree No. 64 dated 24 February 2022, “On the Introduction of Martial Law in Ukraine”, introduced martial law throughout Ukraine.